Peranana Kepemimpinan Kepala Sekolah dalam Meningkatkan Motivasi Kerja Guru di SD Negeri 146 Palembang - Apriana, Leni; Widayatsih, Tri; Nurlina, Nurlina (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to describe the role of school principals in increasing teacher work motivation, the obstacles faced by school principals in increasing teacher work motivation and solutions in overcoming these obstacles. The research method used is a qualitative research method, with the research location at SD Negeri 146 Palembang, South Sumatra. Data collection techniques using interviews, observation, and documentation, with data analysis techniques in the form of data reduction, data presentation/display, and conclusions. The results obtained in this research indicate that the role of the principal as a leader in optimizing teacher performance is good, because several indicators include paying attention to a neat and clean work environment, providing seminars/training meetings, discipline, encouragement, rewards, as well as providing resources or facilities. The infrastructure is quite good, while the teacher's work motivation is quite good, because several indicators are: the teacher's responsibility in carrying out the task, the feeling of joy at work, satisfaction at work, the existence of needs that must be met, enthusiasm for work, the joy of receiving praise, encouragement from superiors, interpersonal relationships and a good work environment.